To evaluate the effect of a structured training program about polycystic ovarian syndrome on the knowledge and perception of nursing students of a government nursing teaching institute in Northern India - Latika Duhan; Rashmi Choudhary; Pushpa Dahiya (Journal of Family Medicine and Primary Care)
Background: The education levels of females have been found to aid in the early detection of polycystic ovary syndrome (PCOS). Early diagnosis and treatment are crucial in mitigating the long-term consequences of PCOS. Nursing students are poised to become the next generation of healthcare professionals, equipped with valuable knowledge that can be utilized to increase awareness among their peers and patients, particularly about this critical subject matter. Objective: We conducted this study to assess the current level of knowledge and perception regarding PCOS among nursing students and to evaluate the impact of structured training interventions on their baseline knowledge and perception level. Methods: It was a single-group pre-post interventional study done on the nursing students of Govt. Nursing College. A pre-tested questionnaire was used as a study tool. Intervention in the form of a structured training program was imparted to the participants. Results: The pre-test group exhibited a lower mean knowledge score (M = 22.5758, SD = 11.02290) than the post-test group (M = 31.3889, SD = 14.50417). A significant difference was observed in the mean knowledge scores (t = −8.107070, P = 0.00001). The pre-test group exhibited a lower mean perception score (M = 35.3535, SD = 3.79637) than the post-test group (M = 36.6616, SD = 3.79576). There was a significant difference in the mean perception score (t = −5.883333, P = 0.00001). Conclusions: This study has shown the positive impact of relevant training on the knowledge and perception of nursing students about PCOS.